Pengembangan Soal Matematika Model TIMSS di Kelas IV Sekolah Dasar - Agustine, Putri Cahyani (Scientia: Jurnal Hasil Penelitian, 2018)
Mathematics is a universal science that underlies the development of modern technology that has an important role in various scientific disciplines and advances human thinking power. One of the achievements of Indonesian students in the field of mathematics, can be seen based on the 2011 TIMSS ranking in which Indonesia ranked 38th of 42 participating countries. One of the factors that causes the low TIMSS results is because the TIMSS model questions in its lesson that have moderate and high complexity, and require reasoning in the completion process. Therefore, researchers were interested in developing mathematical question with TIMSS model in the fourth grade of elementary school. The development of these questions was done through two stages, namely the preliminary study stage, the preparation stage and the formative evaluation stage which included self-evaluation, prototyping (expert reviews, one to one, and small group), and the test field. In this study, there were ten questions categorized as valid and practical qualitatively and quantitatively.